Idiopathic Intracranial Hypertension: Neuropsychiatric Systemic Lupus Erythematosus or Gonadotropinreleasing hormone agonist side effect? - Ong Ping Seung; Ng Yong Muh; Khor Chiew Gek (Rheumatica Acta: Open Access - Peertechz Publications, 2017)
A 31-year-old systemic lupus erythematotus (SLE) patient presented with headache and blurring of vision. Prior to this, she received 2 doses of monthly triptorelin for endometriosis. On examination, she had bilateral sixth nerve paresis. The diagnosis of idiopthic intracranial hypertension (IIH) was confi rmed by an increased intracranial pressure and normal neuroimaging studies of the brain. After releasing the cerebrospinal pressure and cessation of triptorelin, the clinical symptoms resolved without further  treatment. It is important to identify the drugs causing IIH rather than attribute to neuropsychiatric SLE to prevent unnecessary treatment.